Dietary intake of micronutrient and Basal Metabolic Index of women in rural Pakistan - MUHAMMAD ISRAR; SALEEM KHAN; AURANGZEB AURANGZEB; ABID ALI (Nusantara Bioscience, 2017)
Setyawan. 2017. Dietary intake of micronutrient and Basal Metabolic Index (BMI) of women in rural Pakistan. Nusantara Bioscience 9: 396-402. Population’s consumption of essential nutrients and defense against diseases is best indicated by the nutritional status of the individual. Asian women as the central player of the family and, therefore, they propagate the ill effects of malnutrition to generation. In this study, nutritional status and micronutrients (dietary minerals and vitamins) intake of rural women in Pakistan were investigated. One district of Khyber Pakhtunkhwa was selected, out of which, three villages were selected. From each village, 50 rural women were selected for the study. Information about food intake was obtained by a questionnaire. Nutrients intake was obtained from details of food intake in questionnaire, namely, 523 mg/day of calcium; 773 mg/day of phosphorus; 28 mg/day of Iron; 11 mg/day of zinc; 6.61 mg/day of Iodine; 172 R.E./day of Vitamin-A; 21 mg/day of Vitamin-C; 2.79 mg/day of Niacin; 0.31 mg/day of Thiamine; 0.32 mg/day of Riboflavin. The Basal Metabolic Index (BMI) was observed between 19.6 and 52.2 with a mean of 28.54. The study concluded that women’s proportion on consuming mineral and vitamins according to RDA was very small, similarly, the proportion of women in a normal range of BMI was also very small and the curve for BMI suddenly changes direction to the right which confirms that the overweight and obese rural women population was quite common.